The Importance of Results-Based Management in Promoting Transparency and Accountability for Improved Development Initiatives - Prabha, P.V.; Radha, P.; Sharath Kumar, Y. (Madhesh Journal of Interdisciplinary Research, 2026)
Results-Based Management (RBM) is an organizational approach centered on goals and measurable performance, whose global uptake accelerated after the 2005 Paris Declaration on Aid Effectiveness. Prioritizing outcomes and impacts over inputs and activities, RBM is especially pertinent to strengthening governance and effectiveness in development interventions. This literature review examines how RBM fosters transparency and accountability by clarifying objectives, improving performance measurement and reporting, and promoting evidence-based decision-making. Implemented within transparent frameworks, RBM enables stakeholders to participate more effectively, monitor progress, and understand organizational performance against development goals. Synthesizing evidence from multilateral agencies, bilateral donors, development banks, and international NGOs, the analysis links core RBM principles with New Public Management (NPM) to show how RBM cultivates institutional openness, responsibility, and answerability for results. Findings suggest that RBM can build donor and stakeholder trust through clearer strategic planning, demonstrable effectiveness, and documented impact. Persistent technical, political, and capacity constraints, however, limit full implementation. To improve outcomes while sustaining transparency and accountability, the review recommends strengthening RBM via adaptive management, targeted institutional capacity-building, and incentive systems that reward meaningful, sustainable results rather than short-term gains.